Програмне забезпечення оцінки розвитку будівельних підприємств - Антропов, Ю. В. (Ways to Improve Construction Efficiency, 2013)
The estimation accuracy of forecasting bankruptcy of enterprises. Proposed recommendation concerning the use of such models for the analysis of construction enterprises. This article is devoted to the problem of accuracy of forecasting economic sustainability of small enterprises using software based on Excel.